Ritual, performance, and politics in the ancient Near East - Ristvet, Lauren (Cambridge University Press, 2014)
In this book, Lauren Ristvet rethinks the narratives of state formation by investigating the interconnections between ritual, performance, and politics in the ancient Near East. She draws on a wide range of archaeological, iconographic, and cuneiform sources to show how ritual performance was not set apart from the real practice of politics; it was politics. Rituals provided an opportunity for elites and ordinary people to negotiate political authority. Descriptions of rituals from three periods explore the networks of signification that informed different societies. From circa 2600 to 2200 BC, pilgrimage made kingdoms out of previously isolated villages. Similarly, from circa 1900 to 1700 BC, commemorative ceremonies legitimated new political dynasties by connecting them to a shared past. Finally, in the Hellenistic period, the traditional Babylonian Akitu festival was an occasion for Greek-speaking kings to show that they were Babylonian and for Babylonian priests to gain significant power.